The battle-ax people; beginnings of Western culture. - Vlahos, Olivia; Ford, George, 1936- (New York, Viking Press, 1968)
Traces the movements and conquests of the warlike plains people who came from the steppes of southern Russia, giving special attention to the invasions of Greece and Rome and describing the mutual influence of the conqueror and conquered. Includes a history of the English language.
Bibliography: p. [209]-218.
Keywords: Civilization, Ancient